The use of metadiscourse in spoken interlanguage of EFL learners: A contrastive analysis - Kızıl, Aysel Şahin (My University, 2017)
Considered as one of the indispensable parts of spoken communication, metadiscourse is defined as the self-reflective linguistic devices used to organize discourse and signal speakers stance towards the listener and/or towards the content of the communication without adding anything to the propositional content. Insights into the significance of metadiscourse as a means of facilitating communication, supporting position and increasing comprehension have led to an upsurge of interest in researching the use of metadiscourse from a variety of perspectives focusing mainly on written language, albeit with little concern for spoken language. Learner language studies have also tended to investigate the metadiscourse focusing mostly on written interlanguage, leaving the spoken language by learners mostly unexplored. This study investigates metadiscoursal features in Turkish EFL learners’ spoken interlanguage within the framework of Contrastive Interlanguage Analysis based on the two well-known interlanguage corpora (i.e. LINDSEI-TR and LOCNEC) as the data source. Findings of the study are discussed and presented in connection with pedagogical implications for spoken English.
Bildiri - Yayımlanmış
Keywords: EFL learners; Contrastive interlanguage analysis; Learner corpora; Metadiscourse